Lessons from the South: Research Collaboration as an Educational Practice - Danny Wildemeersch; Jan Masschelein (Social Sciences, 2018)
Between 1998 and 2011, we coordinated three consecutive research projects in three different provinces of Northern Vietnam. The projects aimed at improving the living conditions of various ethnic minorities in these areas. We focused on poverty alleviation, water management, and nature conservation. In all cases, there was a close collaboration between Vietnamese and Belgian researchers. The participation of the local population was an important ambition in the research. In this paper, we describe the three projects and analyze the relationships among the Belgian and Vietnamese researchers on the one hand, and between the researchers, the authorities, and the local population on the other hand. Furthermore, we examine the opportunities and obstacles to interdisciplinary and intercultural cooperation, with the help of critical theories on participation and decolonization. The three consecutive research projects can be considered as intensive learning processes for the researchers, the local communities, and the authorities. The paper begins with a fragment from the log of one of the participating researchers.